The management of bond investments and trading of debt - Χωραφάς, Δημήτρης Ν. (Oxford : Elsevier Butterworth-Heinemann, 2005)
Written for managers and professionals in business and industry, and using a minimum of mathematical language, The Management of Bond Investments and the Trading of Debt addresses three key issues: Bondholders options, risks and rewards in making investments in debt instruments; The dynamics of inflation, and how they affect both trading in the bond market, and investment decisions; and The democratization of lending, socialization of risk, and effect of the global economy on the bond market. Financial expert Dimitris Chorafas discusses these issues in straightforward language for managers and professionals in commercial banks, securities houses, financial services companies, merchandising firms, manufacturing companies, and consulting firms, placing the mathematical treatment of the issues in the appendices, available for study but not necessary for understanding the business issues addressed in the book. Focuses on new issues of central importance in bond and debt trading today Uses clear, straightforward language for managers and professionals in business and industry, with mathematical treatment provided in appendices Thorough treatment of operational risk new to books on this topic.
Part One: The Dynamics Of Debt, Leverage, And Globalization -- Ch 1: Democratization Of Lending And Socialization Of Risk -- Ch 2: Trading Debt In A Globalized Economy -- Part Two: The Bondholders Options, Risks And Rewards -- Ch 3: Bonds Defined -- Ch 4: Convertible Bonds, Zero Bonds, Junk Bonds, Strips, And Other Bonds -- Ch 5: Choosing Bonds -- Ch 6: Bank Loans And Securitization; -- Part Three: Interest Rates, Yields, And Duration -- Ch 7: The Dynamics Of Interest Rates -- Ch 8: Inflation Indexing And Impact Of Government Deficits -- Ch 9: Bond Yields and Benchmark Government Bonds -- Ch 10: Maturity And Duration -- Part Four: Bonds, Bond Markets, Credit Rating And Risk Control: -- Ch 11: Bonds, Money Markets, Capital Markets, And Financial Organizations -- Ch 12: Credit Quality And Independent Rating Agencies -- Ch 13: Case Studies On Credit Quality -- Ch 14: Market Risk With Bonds -- Ch 15: The Control Of Risk Under Basel II.
Περιέχει βιβλιογραφία.
Ηλεκτρονικό βιβλίο
Keywords: Bonds; Bond transfer; Debt; Electronic books